The fine structure of dark or intercalated cells from the distal and collecting tubules of avian kidneys - Nicholson,JK; Kendall,MD (Journal of Anatomy, 1983)
Dark or intercalated cells were identified in the terminal portion of the distal tubules and in the intralobular collecting tubules of four species of birds. The morphological features of these cells varied only slightly from species to species and were very similar to cells found in topographically analogous regions of mammalian nephrons. Characteristic vesicles usually filled the apical region of the dark cells and were often in direct continuity with the apical plasma membrane which was frequently thrown into elaborate folds, microvilli and microplicae. Observations suggested that the cells might be involved in some form of cyclical secretory activity. The similarity in structure between avian and mammalian dark cells suggested that they might perform similar functions and that the study of avian cells might aid the elucidation of the mammalian cell function. The possible function of the avian cells were discussed in relation to physiological studies in mammalian kidneys and it was suggested that they might be involved with proton and potassium pumping and control of urinary buffer concentrations.